1999
DOI: 10.1021/bi9821317
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Is Essential for a Single Keratinocyte Growth Factor Molecule To Bind and Form a Complex with Two Molecules of the Extracellular Domain of Its Receptor

Abstract: Keratinocyte growth factor (KGF or FGF-7) is a member of the heparin binding fibroblast growth factor (FGF) family and is a paracrine mediator of proliferation and differentiation of a wide variety of epithelial cells. To examine the stoichiometry of complexes formed between KGF and its receptor, we have utilized a soluble variant of the extracellular region of the KGF receptor containing two tandem immunoglobulin-like loops, loops II and III (sKGFR). Ligand-receptor complexes were examined by size exclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 57 publications
3
37
0
1
Order By: Relevance
“…A comparison of NK1 and c-Met-Fc retention by immobilized heparin-TSK using high performance liquid chromatography gave results consistent with those obtained using the biotin-HS ELISA and also revealed that a control Fc protein was not retained by immobilized heparin (data not shown). Thus, by all of the means used here to compare HS binding by ligand and receptor for the HGF/c-Met system, results were generally similar to those reported for other growth factor/ receptor systems, such as FGFs 1, 2, and 7 (23,35,37,38).…”
Section: C-met Binds Tightly To Hs Via Its Extracellular Domain-supporting
confidence: 81%
See 3 more Smart Citations
“…A comparison of NK1 and c-Met-Fc retention by immobilized heparin-TSK using high performance liquid chromatography gave results consistent with those obtained using the biotin-HS ELISA and also revealed that a control Fc protein was not retained by immobilized heparin (data not shown). Thus, by all of the means used here to compare HS binding by ligand and receptor for the HGF/c-Met system, results were generally similar to those reported for other growth factor/ receptor systems, such as FGFs 1, 2, and 7 (23,35,37,38).…”
Section: C-met Binds Tightly To Hs Via Its Extracellular Domain-supporting
confidence: 81%
“…Ligand binding by that construct was not dependent on added heparin, whereas ligand binding and signaling by wildtype KGF receptor expressed on cell surfaces was significantly enhanced by HS (37). The explanation for this apparent discrepancy became clear after another, independent study of KGF receptor-HS interaction was published (38). Unlike the Ig-receptor chimera used by LaRochelle et al (37), which contained the Ig hinge region and was secreted as a disulfidelinked receptor dimer, Hsu et al (38) showed HS-dependent KGF binding by a soluble monomeric KGF receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os modelos de Pantoliano e colaboradores e de Springer e colaboradores, embasados na estrutura do complexo receptor-ligante do hormônio do crescimento, propõem uma estequiometria de 1FGF:2FGFR:1HEP Springer et al, 1994). Já outros (Xu et al, 1992;Kan et al, 1993;Digabriele et al, 1998; Moy et al, 1997;Huhtala et al, 1999, Hsu et al, 1999 propõem uma estequiometria de 1FGF:1FGFR ligados por 1 ou 2 cadeias de HEP ou HS, formando complexos ternários com FGF-FGFR (Wang et al, 1999).…”
Section: Dados Estruturais Dos Componentes Do Complexo Formado Por Fgunclassified